P84 Pediatric oncology studies triggered by the united states (US) food and drug administration (FDA) and the european union (EU) european medicines agency (EMA) aim at labels, not at improved treatment. Some harm young patients by exposing them to substandard monotherapy instead of combination treatment. Issue 6 (17th May 2019) - Rose, K
Abstract : Background: Both FDA and EMA reward/demand pediatric oncology studies. Do they advance pediatric cancer care? Methods: We analysed publications of FDA representatives, 1–3 FDA-triggered pediatric oncology studies in the literature and in www.clinicaltrials.gov, 4 and FDA/EMA pediatric reports. 5–6 Results: FDA authors express two key assumptions: (1) children, defined as < 17y, need separate proof of efficacy; 1–3 (2) with the exception of chronic myelogenous leukema, the biology of cancer in children is different from adult cancer. 1 FDA-triggered studies investigated single cytoxics agents in heavily pretreated refractory/relapsed patients < 21y. 2 4 In these days, combination treatment with up to 13 cytotoxic agents was standard of care. 7 Another round of treatment with a single chemotherapy agent did not increase survival, but rewarded companies with patent extension, researchers with publications, the FDA with labeled information. The EU expanded the definition of children to < 18y and demands 'pediatric investigation plans' (PIPs) also for rare diseases. One FDA-triggered package investigated ipilimumab in 'pediatric' melanoma; 13 EMA PIPs demand 'pediatric' studies in solid tumors including melanoma; two 'pediatric' monotherapy studies with ipilimumab and vemurafenib, respectively, were terminated in 2016, five others continue recruiting. 3 4 8 Discussion: FDA/EMA-requested/demanded 'paediatric' oncology studies focus on labels in administratively defined 'children'. FDA/EMA-used age limits are not physiological. FDA assumptions about different biology of 'pediatric' malignancies are incorrect. 3 4 8 9 FDA/EMA reports list regulatory, not therapeutic achievements. 5–6 Some EU researchers perform predominantly PIP-demanded oncology studies. In a cartel-like cooperation, the EMA demands such studies, threatening non-approval of life-saving drugs. Researchers and EMA representatives co-author lauding reports. 10 Conclusion: FDA representatives augmented the flawed 'therapeutic orphans' concept by additional wrong assumptions about 'paediatric' malignancies´ biology. 1–4 The EMA further expanded the 'Paediatric Imperative'. Also PIPs do not advance treatment. Ethics committees should be alerted to re-analyze ongoing 'pediatric' studies, suspend questionable ones, and reject new ones. US+EU pediatric laws need revision. References: Snyder KM, et al. The impact of the written request process on drug development in childhood cancer Pediatr Blood Cancer . 2013;60:531–537. Wharton GT, et al. Impact of pediatric exclusivity on drug labeling and demonstrations of efficacy Pediatrics . 2014;134(2):e512–e518. Roberts R, et al. Pediatric Drug Labeling. Improving the Safety and Efficacy of Pediatric Therapies JAMA . 2003;290(7):905–911. Rose K, Grant-Kels JM. Pediatric Melanoma - The Whole (Conflicts Of Interest) Story Int J Womens Dermatol 2018 FDA. Best Pharmaceuticals for Children Act and Pediatric Research Equity Act. July 2016. Status Report to Congress Department of Health and Human Services . EMA. 10-year Report to the European Commission. General report on the experience acquired as a result of the application of the Paediatric Regulation. Norris RE, Adamson PC. Challenges and opportunities in childhood cancer drug development Nat Rev Cancer . 2012 Nov;12(11):776–82. Rose K, Walson PD. Are Regulatory Age Limits in Pediatric Melanoma Justified? Curr Ther Res Clin Exp . 2019 Pappo AS. Pediatric melanoma: the whole (genome) story. Am Soc Clin Oncol Educ Book . 2014:e432–5. Ruperto N et al . A European Network of Paediatric Research at the European Medicines Agency (Enpr-EMA). Arch Dis Child . 2012 Mar;97(3):185–8. Disclosure(s): The author has worked for more than 20 years in research & development/medical affairs in pharma¬ceutical industry and is now an independent consultant, advising pharmaceutical companies and academic institutions in all aspects of pediatric drug development, organizing scientific conferences, publishing, & more. The author´s elder daughter is severely handicapped with a rare syndrom, which has biased him against empty governmental promises.